Obligational Constructions in New Indo-Aryan Languages of Western India - Khokhlova, Liudmila V. (Lingua Posnaniensis, 2013)
The paper describes historical roots as well as syntactic and semantic properties of the three main obligational constructions in modern Hindi-Urdu, Punjabi, Rajasthani 1 and Gujarati2 These constructions differ from one another by the degree and by the type of obligation. The main syntactic properties of obligational constructions discussed in the paper are Agent marking and long distance agreement rules. It will be demonstrated that the increasing frequency of the Dative instead of the Instrumental Agent marking in constructions of obligation was part of the gradual destruction of the ‘passive syntax’ typical for the climactic stage of ergative development.